Caliban's war - Corey, James S. A. (Corey, James S. A. Expanse, 2012)
We are not alone. The alien protomolecule is clear evidence of an intelligence beyond human reckoning. No one knows what exactly is being built on Venus, but whatever it is, it is vast, powerful, and terrifying. When a creature of unknown origin and seemingly impossible physiology attacks soldiers on Ganymede, the fragile balance of power in the Solar System shatters. Now, the race is on to discover if the protomolecule has escaped Venus, or if someone is building an army of super-soldiers. Jim Holden is the center of it all. In spite of everything, he's still the best man for the job to find out what happened on Ganymede. Either way, the protomolecule is loose and Holden must find a way to stop it before war engulfs the entire system.